THE CORRECTOR ARTIFICIAL INTELLIGENCE APPLICATION FOR AUTOMATIC ASSESSMENT OF ESSAY QUESTIONS: AN INNOVATIVE SOLUTION TO IMPROVE STUDENTS' HOTS IN PURWAKARTA - Ilyas, R. Marpu Muhidin; Darojat, Jajat (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study examines the development of an artificial intelligence (AI)-based application called The Corrector for automatic assessment of essay questions in Purwakarta, West Java. The aim is to overcome the limitations of multiple-choice questions in evaluating students' high-level thinking skills (HOTS)and reduce the burden on teachers. The methods include application development using ChatGPT API, PHP, Python, Jquery, and teacher and student perception surveys. The results show increased efficiency and accuracy of assessment and positive responses from teachers and students. Policy recommendations include gradual implementation of AI applications, teacher training, and ongoing evaluation to improve the quality of education in Purwakarta.